2019
DOI: 10.1590/s1984-29612019004
|View full text |Cite
|
Sign up to set email alerts
|

Pupipara (Diptera, Hippoboscidae) in wild birds attended at a rehabilitation center in southern Brazil

Abstract: The hippoboscids are cosmopolitan permanent obligate hematophagous ectoparasites of birds, domestic and wild mammals and, occasionally, humans. Some species may act as vectors or hosts of etiological pathogenic agents. The aims of this study were to report on the first cases of Hippoboscidae in Crax blumenbachii and Parabuteo unicinctus; to provide new reports from Brazil on Tyto furcata and Asio stygius parasitized by Icosta americana; to report on individuals of Bubo virginianus, Falco sparverius and Accipit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 6 publications
(7 reference statements)
2
3
0
Order By: Relevance
“…Few reports on O. erythrocephala from Brazil described the number of individuals collected per bird. These reports frequently describe the presence of only one or two specimens parasitizing each bird (Tossas, 2001;Graciolli & Bispo, 2005;Moreira et al, 2019), similar to what was described in the present report, where only one specimen was recovered. The rapid flight of the Hippoboscid species may be the reason why so few individuals are recovered from infested birds (Johnson, 1925).…”
Section: /5supporting
confidence: 84%
“…Few reports on O. erythrocephala from Brazil described the number of individuals collected per bird. These reports frequently describe the presence of only one or two specimens parasitizing each bird (Tossas, 2001;Graciolli & Bispo, 2005;Moreira et al, 2019), similar to what was described in the present report, where only one specimen was recovered. The rapid flight of the Hippoboscid species may be the reason why so few individuals are recovered from infested birds (Johnson, 1925).…”
Section: /5supporting
confidence: 84%
“…Hippoboscids flies are parasites usually associated with birds of prey (Accipitriformes, Cathartiformes, Falconiformes and Strigiformes) and pigeons (Columbiformes). Although less frequent, in Brazil hippoboscids were also collected on Passeriformes, Piciformes and Galliformes (Moreira et al, 2019, Vélez et al, 2020Gomes et al, 2021), corroborating other studies (Murgas et al, 2014;Barino et al 2021;Graciolli, Bispo, 2005;Graciolli and Oak, 2003;Liébana et al, 2011).…”
supporting
confidence: 85%
“…(Barino et al, 2021). Vaz and Teixeira (2016) and Moreira et al (2019) reported parasitism by Ornithoctona erytrocephala and Icosta americana in avian, occurring in the Brazilian South and Southeast regions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…In Brazil, studies (Lutz et al, 1915;Bequaert, 1954;Maa, 1969;Graciolli and Carvalho, 2003;Graciolli and Bispo, 2005;Serra-Freire and Quadros, 2013;Lambrecht et al, 2015;Vaz and Teixeira, 2016;Graciolli et al, 2017;Moreira et al, 2019).…”
Section: Resultsmentioning
confidence: 99%